Pandangan Keagamaan Pelaku Bom Bunuh Diri di Indonesia - Herlina Nurani; Ahmad Ali Nurdin (UIN Walisongo Semarang, 2018)
This journal discusses most of the religious discussions launched in Indonesia. This research is library research. Is the result of being found first, understanding the religious texts textually. Second, there are differences of opinion that influence the text that improves development that accommodates modernization theories, thereby increasing disappointment with the government. Third, the existence of understanding as jihad is a holy war against unbelievers because it considers the government system in Indonesia to be changed based on the justice of their religious understanding.Keyword: globalization; religion; radicalism; jihad; AbstrakJurnal ini menelusuri tentang sebagian pandangan keagamaan pelaku bom bunuh diri di Indonesia. Penelitian ini adalah library riset. Adapun hasil yang ditemukan pertama, pemahaman nash-nash agama secara tekstual. Kedua, adanya sikap protes yang mempengaruhi pemahaman teks serta kegagalan pembangunan yang mengakomodasi teori-teori modernisasi, sehingga terjadinya kekecewaan terhadap pemerintah. Ketiga, adanya paham bahwa jihad adalah perang suci sebagai perang untuk melawan orang kafir karena menganggap sistem kepemerintahan di Indonesia harus dirubah berdasarkan kebenaran pemahaman keagamaan mereka. Kata Kunci : globalisasi; agama; radikalisme; jihad;